IRON METABOLISM AND INTESTINAL IRON ABSORBTION IN CHRONIC GASTRITIS - Попович, Мирослава (SWorldJournal, 2023)
The problem of treatment of chronic gastritis in servicemen, as one of the most common diseases of the gastrointestinal tract, is especially relevant in the light of the evidence on the determining role H. pylori infection in the progression of the diseas